Agribusiness System Hub for Rural Agrarian Management - Dmytro G. Shushpanov, Ruslan R. Avhustyn, Nadvynychnyy Sergiy, Irina O. Demkiv, Borys O. Yazlyuk (International Journal of Advanced Science and Technology, 2020)
Agribusiness is suggested to understand everyone’s activities spheres of the agro-industrial complex, and the phrase «agrarian production» and «agricultural production» to be synonymous. It is proved that agricultural and industrial production as types of eco-number of activities that qualitatively differ from each other as sources of income. This is because for agriculture is characterized by a declining return on resources, and a growing one for industry. The drop-resource giving leads to reduced productivity of resources, including labour and wages, and growing – to increase resource productivity and payroll. That is why in countries with agrarian and mining economies quantitatively and qualitatively lower revenues from sales of products compared to industrial countries we. Agroindustrial formations combine agriculture and industry, making them competitive advantage over other forms of agribusiness. The clarification of basic concepts of agrarian management and agribusiness, and the characteristics of agriculture and industry as types of economic activities and branches of agro-industrial formations will allow to expand and systematize scientific research in agrarian economy and management.